2008
DOI: 10.4103/0256-4947.51699
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy for benign conditions in a university hospital in Saudi Arabia

Abstract: BACKGROUND AND OBJECTIVEHysterectomy is a common surgical procedure among women with a lifetime prevalence of 10%. The indications and complications of this procedure have not been previously reported from a teaching institution in Saudi Arabia. We examined the indications for hysterectomy and the surgical morbidity for women undergoing hysterectomy at a university hospital in Saudi Arabia.PATIENTS AND METHODSWe reviewed the records of women who underwent hysterectomies for benign gynecological conditions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…In contrast to other studies from Germany [9], France [10], and Finland [11] more hysterectomies are performed vaginally than abdominally. Previous studies [6] [8] [9] reported that vaginal approach mainly used in patients with uterine prolapse that is similar to our results.…”
Section: Discussionmentioning
confidence: 46%
“…In contrast to other studies from Germany [9], France [10], and Finland [11] more hysterectomies are performed vaginally than abdominally. Previous studies [6] [8] [9] reported that vaginal approach mainly used in patients with uterine prolapse that is similar to our results.…”
Section: Discussionmentioning
confidence: 46%
“…In review of literature, leiomyoma uterus is the most common indication for hysterectomy worldwide. [78910111213] However, our observation of POP being the most common indication for benign gynecological surgery could be due to higher number of unsupervised home conducted vaginal births with tendency for premature bearing down during labor in rural and tribal populations. Younger women in third decade of life were offered conservative approach of Fothergill's operation and Purandare's cervicopexy, whereas definite surgery, that is, VH with pelvic floor repair was done in elderly women.…”
Section: Discussionmentioning
confidence: 99%
“…In review of literature also, fibroid uterus is reported as the most common indication for hysterectomy worldwide. 16,[18][19][20][21] However, there has been controversy regarding indications for hysterectomy for benign gynecological diseases in Indian subcontinent. 22 Of total, only 6% surgeries were done for premalignant cervical lesions in the study which conclude that rural women with cervical malignancy usually present late due to lack of awareness, non availability of adequate screening tests and pathologists.…”
Section: Discussionmentioning
confidence: 99%